2002
DOI: 10.1103/physreva.66.053608
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of dark solitons with localized impurities in Bose-Einstein condensates

Abstract: We study the interaction of dark solitons with a localized impurity in Bose-Einstein condensates. We apply the soliton perturbation theory developed earlier in optics for describing the soliton dynamics and solitonimpurity interaction analytically, and then verify the results by direct numerical simulations of the Gross-Pitaevskii equation. We find that a dark soliton can be reflected from or transmitted through a repulsive impurity in a controllable manner, while near the critical point the soliton can be qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
155
1
3

Year Published

2004
2004
2012
2012

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 102 publications
(172 citation statements)
references
References 40 publications
13
155
1
3
Order By: Relevance
“…Apparently, this issue is important for applications, since it would demonstrate a possibility of driving the dark solitons (and other coherent structures, more generally) in the BEC by means of OL potentials. Note that it has been recently shown that an attractive steadily moving localized impurity may drag a stationary DS [10], but here we aim to consider the more general problem of the targeted transfer of a dark soliton by an OL.…”
Section: Intermediate Optical Lattice Periodmentioning
confidence: 99%
See 4 more Smart Citations
“…Apparently, this issue is important for applications, since it would demonstrate a possibility of driving the dark solitons (and other coherent structures, more generally) in the BEC by means of OL potentials. Note that it has been recently shown that an attractive steadily moving localized impurity may drag a stationary DS [10], but here we aim to consider the more general problem of the targeted transfer of a dark soliton by an OL.…”
Section: Intermediate Optical Lattice Periodmentioning
confidence: 99%
“…Then, we follow the procedure described in Ref. [10] (see also Ref. [13]) to derive the following effective perturbed NLS equation from Eq.…”
Section: The Long-period Optical Latticementioning
confidence: 99%
See 3 more Smart Citations